2022
DOI: 10.7554/elife.72458
|View full text |Cite
|
Sign up to set email alerts
|

An intestinally secreted host factor promotes microsporidia invasion of C. elegans

Abstract: Microsporidia are ubiquitous obligate intracellular pathogens of animals. These parasites often infect hosts through an oral route, but little is known about the function of host intestinal proteins that facilitate microsporidia invasion. To identify such factors necessary for infection by Nematocida parisii, a natural microsporidian pathogen of Caenorhabditis elegans, we performed a forward genetic screen to identify mutant animals that have a Fitness Advantage with Nematocida (Fawn). We isolated four fawn mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 86 publications
(204 reference statements)
0
27
0
Order By: Relevance
“…N2 and aaim-1 mutants (kea22 and kea28) 23 were infected with N. cider (4 million spores) as described above. To quantify pathogen burden within animals (GFP), regions of interest were .…”
Section: Infection Of Aaim-1 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…N2 and aaim-1 mutants (kea22 and kea28) 23 were infected with N. cider (4 million spores) as described above. To quantify pathogen burden within animals (GFP), regions of interest were .…”
Section: Infection Of Aaim-1 Mutantsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 28, 2022. ; https://doi.org/10.1101/2022.08. 28.505597 doi: bioRxiv preprint infection of a host, host immune responses to infection, and identify inhibitors of microsporidian infection [21][22][23][24][25][26][27][28] . Additional species that infect the intestine, N. ausubeli and N. ironsii, have also been identified 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that microsporidia can affect host population dynamics and evolution. Microsporidia have been suggested to influence the composition of Caenorhabditis elegans genotypes and resistant strains can outcompete sensitive ones in just a few generations [18][19][20]. In competition experiments with over a dozen isolates of Daphnia magna, different microsporidia species have been shown to select for specific strains [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds that displayed strong activity against microsporidia infection in the continuous infection assays, but not the pulse-chase infections, may be preventing invasion by inhibiting spore firing. In C. elegans , N. parisii spores are ingested, and spore firing is triggered in the intestinal lumen (27, 48). To test if any compounds interfere with this process, we performed spore firing assays on the 7 compounds with the strongest effect in the continuous infection assays (Fig.…”
Section: Resultsmentioning
confidence: 99%